Small molecule screen yields inhibitors of pseudomonas homoserine lactone‐induced host responses. (22nd August 2013) - Valentine, Cathleen D.; Zhang, Hua; Phuan, Puay‐Wah; Nguyen, Juliane; Verkman, A. S.; Haggie, Peter M.
Summary Pseudomonas aeruginosa infections are commonly associated with cystic fibrosis, pneumonias, neutropenia and burns. The P. aeruginosa quorum sensing molecule N‐(3‐oxo‐dodecanoyl) homoserine lactone (C12) cause multiple deleterious host responses, including repression of NF‐κB transcriptional activity and apoptosis. Inhibition of C12‐mediated host responses is predicted to reduce P. aeruginosa virulence. We report here a novel, host‐targeted approach for potential adjunctive anti‐Pseudomonal therapy based on inhibition of C12‐mediated host responses. A high‐throughput screen was developed to identify C12 inhibitors that restore NF‐κB activity in C12‐treated, lipopolysaccharide (LPS)‐stimulated cells. Triazolo[4, 3‐a]quinolines with nanomolar potency were identified as C12‐inhibitors that restore NF‐κB‐dependent luciferase expression in LPS‐ and TNF‐stimulated cell lines. In primary macrophages and fibroblasts, triazolo[4, 3‐a]quinolines inhibited C12 action to restore cytokine secretion in LPS‐stimulated cells. Serendipitously, in the absence of an inflammatory stimulus, triazolo[4, 3‐a]quinolines prevented C12‐mediated responses, including cytotoxicity, elevation of cytoplasmic calcium, and p38 MAPK phosphorylation. In vivo efficacy was demonstrated in a murine model of dermal inflammation involving intradermalC12 administration. The discovery of triazolo[4, 3‐a]quinolines provides a pharmacological tool to investigate C12‐mediated host responses, and a potential host‐targeted anti‐Pseudomonal therapy.